PERANCANGAN DAN PEMANFAATAN SAKELAR ELEKTRONIK (ELECTRONIC SWITCH) - Dwi Feriyanto Dwi; Ancolo; Yenni Afrida; Soleh Zainuri; Wahyu Ponco Aji (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2021)
The Switch is a tool that everyone knows its use in everyday life. Switch functions as a breaker and connector of an electrical or electronic equipment. Switches are divided into 2 types, namely: mechanical switches and electronic switches. Mechanical switches are made of metal / copper, while electronic switches are made of a semi-conducting material called transistors, which are coupled with other electronic components. The design methode consists of design block design, work system, and design trials. The results obtained are in the form of a prototype electronic circuit called an electronic switch which uses several electronic components such as: resistors, electrolytic capacitors, integrated circuits, diodes, transformers, and relays.